1999
DOI: 10.1063/1.123622
|View full text |Cite
|
Sign up to set email alerts
|

Non-Gaussian behavior and anticorrelations in ultrathin gate oxides after soft breakdown

Abstract: The time dependence of the gate voltage VG(t) after soft breakdown of metal-oxide-semiconductor capacitors with a 2.4 nm SiO2 layer has been measured. It is found that the VG(t) fluctuation distributions are non-Gaussian, but can be described by a Lévy stable distribution. The long-range correlations in VG(t) are investigated within the detrended fluctuation analysis. The Hurst exponent is found to be H=0.25±0.04 independent of the value of the stress current density J. It is argued that these are universal fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 10 publications
2
39
0
1
Order By: Relevance
“…Since a further increase of the stress voltage causes the film to break down, the emerging non-Gaussian distribution can be thought of as a precursor of failure as observed in experiments [1].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since a further increase of the stress voltage causes the film to break down, the emerging non-Gaussian distribution can be thought of as a precursor of failure as observed in experiments [1].…”
Section: Resultsmentioning
confidence: 99%
“…Starting from the intrinsic value of the network [6], the variance is found to increase significantly as a net effect of the stressing voltage which is ultimately responsible of the breakdown at about 0.9 V . Recent observations of SILC measurements reported non-Gaussian current fluctuations in the soft breakdown region of ultra-thin dielectrics [1]. Therefore, we computed the distribution function of the current fluctuations P (I) for stress voltages of 0.5 V and 0.85 V and plotted them in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of analysis is based on the random walk theory (Shlesinger 1987) and has been found to be almost unbiased for fractal noises and motion (Witt & Malamud 2013), providing an important tool for the detection of long-range (auto-)correlation properties in time-series with nonstationarities. It has been successfully applied to such diverse fields of interest as DNA analysis (Buldyrev et al 1995;Peng et al 1995), heart rate dynamics Ho et al 1997), long-time weather records (Koscielny-Bunde et al 1998;Talkner & Weber 2000), cloud structure (Ivanova & Ausloos 1999) and even solid state physics (Kantelhardt et al 1999;Vandewalle et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the long-range correlations of magnitude series indicate nonlinear behavior and the sign time series mainly relate to linear properties of the original series. The time series analysis methods based on long-range correlation has been successfully applied to diverse fields such as DNA sequences [10][11], long-time weather records [14], geology [15], ethnology [16], physiological dynamics [17] and economics time series [18].…”
Section: Introductionmentioning
confidence: 99%